Geraniol attenuates virulence factors by inhibiting quorum sensing of Pseudomonas aeruginosa - Li, Wen-Ru; Zeng, Tao-Hua; Zhang, Zhi-Qing; Shi, Qing-Shan; Xie, Xiao-Bao (Frontiers in Microbiology, 2023)
Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen that can cause severe respiratory tract infections. Geraniol, a chemical component of essential oils, has antimicrobial and anti-inflammatory activities, along with low toxicity. However, the effect and mechanism of geraniol against P. aeruginosa virulence factors are rarely studied. In this study, we investigated the quorum sensing (QS) inhibitory effects and mechanisms of geraniol against P. aeruginosa PAO1, using physiological and biochemical techniques, quantitative reverse transcription polymerase chain reaction, and transcriptomics. Geraniol slightly affected P. aeruginosa PAO1 growth, prolonged the lag phase, and delayed growth periods in a concentration-dependent manner. Geraniol inhibited three QS systems of P. aeruginosa, las, rhl, and pqs by suppressing the expression level of their key genes, including the three signal synthetase encoding genes of lasI, rhlI, and pqsABCDEH, and the corresponding signal receptor encoding genes of lasR, rhlR, and pqsR. Geraniol also suppressed certain virulence genes regulated by these three QS systems, including rhlABC, lasAB, lecAB, phzABMS, and pelABG, resulting in the attenuation of the related virulence factors, rhamnolipids, exoprotease LasA, elastase, lectin, pyocyanin, and biofilm. In conclusion, geraniol can suppress the virulence factors of P. aeruginosa PAO1 by inhibiting the three QS systems of las, rhl, and pqs. This study is significant for improving the treatment of bacterial infections caused by P. aeruginosa.